Collpa mining tailings, as a stabilizer additive for LM soils for the construction of buildings - Llacza Cardenas, Hans Alexander (2023)
The abandoned mining tailings deposit, located in the town of Collpa in the district of Santa Bárbara de Carhuacayán, province of Yauli, department of Junín, generates serious environmental contamination to the town of the district, above all, it affects the upper basin of the Mantaro river; For this reason, this material was studied for its possible use as a stabilizing additive for a type of soil: ML (Inorganic Silt), for the foundation of constructions. The procedures were laboratory tests that are: Granulometric tests, Atterberg Limits, Standard Proctor Test, Soil Specific Gravity Test, Direct Shear Test and finally, the admissible bearing load of each analyzed sample (qadm) was analyzed; these samples are constituted by the ML soil with the combination of the mining tailings in percentage proportions of 0%, 20%, 30%, 50% with respect to the total weight of each sample. The results of the project, when analyzing and calculating the data obtained from the laboratory tests, were: 5kg/cm2, 4.67kg/cm2, 5.84kg/cm2 and 7.57kg/cm2, which are the qadm of each sample with the proportion of tailings. in ascending order respectively. In conclusion, the studied mining tailings increases the mechanical characteristics of the ML soil, stabilizing it with respect to its base state.